2014
DOI: 10.7554/elife.01386
|View full text |Cite
|
Sign up to set email alerts
|

Mouse rods signal through gap junctions with cones

Abstract: Rod and cone photoreceptors are coupled by gap junctions (GJs), relatively large channels able to mediate both electrical and molecular communication. Despite their critical location in our visual system and evidence that they are dynamically gated for dark/light adaptation, the full impact that rod–cone GJs can have on cone function is not known. We recorded the photovoltage of mouse cones and found that the initial level of rod input increased spontaneously after obtaining intracellular access. This process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 57 publications
9
67
0
Order By: Relevance
“…In addition, rods may have additional functions beyond scotopic light detection. Chemical and electrical rod-cone coupling can mediate mesopic vision (Abd-El-Barr et al, 2009; Asteriti et al, 2014; Hornstein et al, 2005; Pang et al, 2012; Ribelayga and Mangel, 2010). Rods also drive circadian photoentrainment (Altimus et al, 2010) and horizontal cell-mediated surround inhibition of cone signal (Szikra et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rods may have additional functions beyond scotopic light detection. Chemical and electrical rod-cone coupling can mediate mesopic vision (Abd-El-Barr et al, 2009; Asteriti et al, 2014; Hornstein et al, 2005; Pang et al, 2012; Ribelayga and Mangel, 2010). Rods also drive circadian photoentrainment (Altimus et al, 2010) and horizontal cell-mediated surround inhibition of cone signal (Szikra et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the outer retina, gap junctions form electrical synapses among the axons of neighboring rods, between rods and cones, and among cones (Asteriti et al, 2014; DeVries et al, 2002; Tsukamoto et al, 2001). In the mammalian inner retina, the axon terminals of most or all subtypes of ON cone bipolar cells are coupled via gap junctions with the dendrites of AII amacrine cells (Cohen and Sterling, 1990; Marc et al, 2014; Veruki and Hartveit, 2002a) or via gap junctions directly between cone bipolar cells (Cohen and Sterling, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…), as well as rod–cone coupling (Asteriti et al . ). Jin and colleagues are aware of and rightfully concerned about these potential problems, as can be seen from their statement: “A recent study has reported that rod–cone coupling increases spontaneously after obtaining intracellular access in mouse cones and that rundown of kinetics with time are often observed in patched rods (Asteriti et al .…”
mentioning
confidence: 97%
“…Jin and colleagues are aware of and rightfully concerned about these potential problems, as can be seen from their statement: “A recent study has reported that rod–cone coupling increases spontaneously after obtaining intracellular access in mouse cones and that rundown of kinetics with time are often observed in patched rods (Asteriti et al . ). In our conditions, we observed a rundown in rod kinetics following intracellular access in less than 10% of the rods.…”
mentioning
confidence: 97%
See 1 more Smart Citation